Registration of the thermal neutrons using uncooled Si planar detector - Bochek, G.L.; Deiev, O.S.; Kiprich, S.K.; Maslov, N.I.; Shulika, M.Y.; Vasiliev, G.P.; Yalovenko, V.I. (Вопросы атомной науки и техники, 2016)
The registration of thermal neutrons by Si planar detector with natural metallic Gd neutron converter was performed. The ²³⁹Pu-Be(α, n) fast neutron source with flux 1.13·10⁵ с⁻¹ with paraffin moderator for obtaining of thermal neutrons was used. Control measurements of the thermal neutron flux by detector-dosimeter MKS-01R were performed. Experimental spectra for the reaction Gd(n, γ)Gd were measured. Spectra consisted of the spectra conversion electrons in energy range 30…200 keV with maximum at energy ~ 70 keV and Gd CXR lines. Background gamma-radiation was measured by Si PIN detector without Gd plate. Program code GEANT4 for the calculation of the thermal neutron flux was used.